Pengembangan Media Pembelajaran AWA (Al-Qur’an Wahyu Allah) Berbasis iSpring Suite pada Mata Pelajaran Al-Qur’an Hadis Kelas X di MA Al-Bairuny Sambong Dukuh Jombang - Imaniyah, Febriana Hulwatul; Rohmah, Hidayatur (Lembaga Yasin AlSys, 2025)
The teaching of Al-Qur’an Hadith in Grade X at MA Al-Bairuny Sambong Dukuh Jombang remains dominated by lecture methods and a single learning medium—namely, the textbook—which has led to low student engagement and motivation. This study aims to develop the AWA (Al-Qur’an Wahyu Allah) media based on iSpring Suite and analyze student responses regarding its effectiveness. The method used is Research and Development (R&D) following the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection instruments included validation questionnaires from media experts and subject matter experts, as well as student response questionnaires. Validation by media experts resulted in an average score of 89% (valid category) in the first stage and 68% (moderately valid) in the second. Subject matter expert validation yielded scores of 93% and 90%, both categorized as highly valid. Meanwhile, the student response to the AWA media showed a score of 90%, categorized as highly practical. These findings indicate that the iSpring Suite-based AWA media is both feasible and practical for use in Al-Qur’an Hadith learning, particularly in enhancing interactivity and student comprehension of conceptual and sequential material. The study’s implications highlight the importance of utilizing interactive media as an innovative solution to foster more effective and enjoyable learning experiences.